(untitled) (Research, Society and Development, 2025)
Objective: To analyze the epidemiological profile of confirmed cases of pertussis in the metropolitan region of Maringá between 2007 and 2024. Methods: The research was based on data from the National System of Injuries and Notifications (SINAN) to extract epidemiological data and structure the descriptive quantitative study. Results: A total of 222 cases of pertussis were reported. Children under 1 year of age, female, and white are the most affected. Regarding the evolution of these cases, it was found that among the 222 cases, 214 were cured of the disease, 2 deaths were recorded in 2014, and 6 records were considered blank/Ign in the system, having the highest underreporting rate in 2024. Regarding the geographic distribution, among the 26 municipalities analyzed, Maringá had the highest record (55.40%). Conclusions: The findings of this study are in line with other national studies, corroborating that whooping cough is a public health problem, as it shows the increasing number of confirmed cases since 2012, with a peak of 56 cases in 2024. The results indicate the importance of reflecting on public health strategies and actions. It is important to note that whooping cough can be prevented through vaccination. The goal established by the Ministry of Health for whooping cough vaccination coverage is 95%, but this goal has not been achieved. That said, it is important to monitor vaccination coverage rates to promote prevention strategies, early diagnosis, and disease management.